Low-Frequency Broadband Acoustic Metasurface Absorbing Panels - Ji, Jun; Li, Dongting; Li, Yong; Jing, Yun (Frontiers in Mechanical Engineering, 2020)
A broadband sound absorption attained by a deep-subwavelength structure is of great interest to the noise control community especially for extremely low frequencies (20-100 Hz) in room acoustics. In this paper, we report on an analytical, numerical and experimental study of a low-frequency broadband (50-63 Hz, one third octave band), high absorption (average absorption coefficient ≈93%), near-omnidirectional (0° - 75°) acoustic metasurface absorber at a thickness of 15.4 cm (1/45 of the wavelength at 50 Hz). To further broaden the bandwidth (50-100 Hz, one octave band), another design is analytically studied to achieve an average absorption coefficient of 85% for a wide angle range (0°-75°) at a thickness of 20 cm (1/34 of wavelength at 50 Hz). The proposed design methodology may solve the long-standing issue for low frequency absorption in room acoustics.